Animaze Animation @ Cannes Film Festival Market 2023 - Sofokleous, Konstantina (My University, 2026)
'Thread Threat' Officially Selected Screening at Animaze Animation Day in Cannes Animaze Animation @ Cannes Film Festival Market 2023
Keywords: Arts and entertainment